2005
DOI: 10.1002/art.21208
|View full text |Cite
|
Sign up to set email alerts
|

Genetically based resistance to the antiinflammatory effects of methotrexate in the air‐pouch model of acute inflammation

Abstract: Objective. Low-dose methotrexate (MTX), a mainstay in the treatment of rheumatoid arthritis, is effective in only 60-70% of patients, a finding mirrored by poor antiinflammatory efficacy in some animal models, most notably collagen-induced arthritis. To determine whether genetic factors or the model itself is responsible for the poor response to MTX, we directly compared the responses of 4 inbred mouse strains to MTX in the air-pouch model of acute inflammation.Methods. The exudate leukocyte count and adenosin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…In addition, it has been reported that circulating intracellular levels of methotrexate glutamates in red blood cells and polymorphonuclear cells correlate with the clinical efficacy, but no toxicity, in RA [104]. Genetically based resistance to the effects of methotrexate has also been suggested in the airpouch model of acute inflammation [167].…”
Section: Rheumatoid Arthritismentioning
confidence: 98%
“…In addition, it has been reported that circulating intracellular levels of methotrexate glutamates in red blood cells and polymorphonuclear cells correlate with the clinical efficacy, but no toxicity, in RA [104]. Genetically based resistance to the effects of methotrexate has also been suggested in the airpouch model of acute inflammation [167].…”
Section: Rheumatoid Arthritismentioning
confidence: 98%
“…Figure 4 shows several examples of the effects of elmiric acids in the subcutaneous pouch assay using two methods for inducing an inflammatory response, namely, a combination of cytokines in panel A and carrageenan in panel B. The subcutaneous air pouch simulates a synovium lined joint space by providing a blind connective tissue cavity without a mesothelial basement membrane; the pouch lining has the two cell types (fibroblasts and macrophage-like cells) common to synovia [41][42][43] . While the precision of the assay was improved over the paw edema, an unexpected discrepancy arose with the palmitoyl derivatives when carrageenan was the inducer.…”
Section: Anti-inflammatory Effects In Vivomentioning
confidence: 99%
“…Among them, an "air-pouch" murine model has been extensively used to study inflammation (7)(8)(9). This model was adapted further to evaluate the effect of fibrinogen depletion on S. aureus infections (10), as well as to study the host responses to group A Streptococcus infection, and the reduction of infection in mice immunized with specific antigens (11)(12)(13).…”
mentioning
confidence: 99%